The effects of maternal age and parity on birth weight in a tribal community of Kinwat, Nanded, Maharashtra, India - Narwade, Ramdas G.; More, Uttam B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Low birth weight is an important determinant of childhood morbidity and mortality. Birth weight is a significant factor that determines vulnerability of risk of childhood illness and survival. Objective of the study was to correlate the maternal age and parity on birth weight in a tribal community. Methods: A cross-sectional study was carried out during April 2012 to June 2014 in More Nursing Home, Kinwat Dist. Nanded, Maharashtra. A total of 1611 patients from tribal area who delivered in the nursing home were enclosed for the study. Data was analyzed by using SSPS version-18.0. Results: In this study low birth weight babies were seen in 18.56% and 17.78% and 21.47% of female and male babies had low birth weight respectively, which was statistically significant. Mean birth weight increased as parity of mother increased. Low birth weight babies were born to the mother of younger age which was statistically significant. Conclusions: Health care of young age tribal mothers is important factor in curbing low birth weight babies.